2020
DOI: 10.1029/2020gl088578
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Sprite Streamers to the Chemical Composition of the Mesosphere‐Lower Thermosphere

Abstract: Sprites are mesospheric filamentary discharges that liberate and accelerate large quantities of electrons. They produce local enhancements of some chemical species and fast (millisecond) optical emissions. In this work, we couple a self‐consistent 2‐D model of sprites with an extensive chemical scheme to calculate the injection of chemical species by one sprite streamer in the mesosphere 0.85 ms after its onset. The N, NO, and N2O injections per streamer are about 1021 atoms, 6 × 1019 molecules, and 1018 molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Our global and seasonal nighttime thundercloud streamer corona distributions, zonal and meridional averages, and nighttime variability provide the first worldwide view of coronas occurring in thunderstorms. These results can set the path for future studies that should deepen our knowledge on key themes such as types of corona discharges in thunderclouds, morphology (and dynamics) of optical (and radio) emissions from the heads and long-lasting glows of streamers in thundercloud coronas (Luque et al, 2016;Pérez-Invernón et al, 2020), role of meteorological conditions (F. in favoring their initiation/deactivation (Huang et al, 2021) and, finally but no less important, to explore the impact of non-equilibrium (electron driven) chemical reactions triggered by hundreds of millions of streamers in kilometer long cloud coronas (Brune et al, 2021;Gordillo-Vázquez & Pérez-Invernón, 2021) on the atmospheric chemistry of the upper troposphere and lower stratosphere.…”
Section: Discussionmentioning
confidence: 93%
“…Our global and seasonal nighttime thundercloud streamer corona distributions, zonal and meridional averages, and nighttime variability provide the first worldwide view of coronas occurring in thunderstorms. These results can set the path for future studies that should deepen our knowledge on key themes such as types of corona discharges in thunderclouds, morphology (and dynamics) of optical (and radio) emissions from the heads and long-lasting glows of streamers in thundercloud coronas (Luque et al, 2016;Pérez-Invernón et al, 2020), role of meteorological conditions (F. in favoring their initiation/deactivation (Huang et al, 2021) and, finally but no less important, to explore the impact of non-equilibrium (electron driven) chemical reactions triggered by hundreds of millions of streamers in kilometer long cloud coronas (Brune et al, 2021;Gordillo-Vázquez & Pérez-Invernón, 2021) on the atmospheric chemistry of the upper troposphere and lower stratosphere.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the estimated K is highly sensitive to the assumed streamer radius: had we chosen a radius of 5 mm at atmospheric pressure, the estimation of K would be reduced by about a factor 15. It is also possible that a large fraction of the optical signal in fast breakdown is emitted not close to streamer heads but from long‐lived glows, as is the case in sprites (Luque et al., 2016; Pérez‐Invernón et al., 2020).…”
Section: Light‐scattering Modelmentioning
confidence: 99%
“…Test simulations have shown that the sprite altitude region is not significantly affected if different boundary conditions are used, e.g. linearly extrapolated SABER mixing ratios or O and H concentrations from the NRLMSIS-00 model (Picone et al, 2002). The model simulation with fast vertical transport agrees well with the MLS water measurements at altitudes above ∼ 75 km.…”
Section: Background Atmosphere Simulationsmentioning
confidence: 63%